2014
DOI: 10.3102/0034654313499615
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of English-Medium Education in Hong Kong

Abstract: To facilitate second language learning, it has become increasingly popular to use a second language as the medium of instruction for content subjects for majority language students. Although numerous research studies have shown the advantages of such kind of programs in North America and Europe, those investigating English as the Medium of Instruction (EMI) schools in Hong Kong yielded inconclusive results. This meta-analysis is the first attempt to synthesize the research evidence on EMI education in Hong Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 48 publications
4
68
0
3
Order By: Relevance
“…This can be accounted for by the considerable divergence in the foreign language or second language (L2) involved and the different models under the umbrella term CLIL. For instance, Lo and Lo's (2014) meta-analysis about the effectiveness of EMI/CLIL in Hong Kong has revealed that while learners have experienced gains in their L2 proficiency, their knowledge of content subjects has suffered. Cenoz, Genesee, and Gorter (2014) have proposed factors causing discrepancies between learners' improvement in language proficiency and subject learning.…”
Section: Background To the Studymentioning
confidence: 98%
“…This can be accounted for by the considerable divergence in the foreign language or second language (L2) involved and the different models under the umbrella term CLIL. For instance, Lo and Lo's (2014) meta-analysis about the effectiveness of EMI/CLIL in Hong Kong has revealed that while learners have experienced gains in their L2 proficiency, their knowledge of content subjects has suffered. Cenoz, Genesee, and Gorter (2014) have proposed factors causing discrepancies between learners' improvement in language proficiency and subject learning.…”
Section: Background To the Studymentioning
confidence: 98%
“…Studies of EMI education in Hong Kong are less conclusive. Recent large-scale studies tend to suggest that EMI helps with L2 learning, but is less beneficial to academic progress (Hong Kong Education Bureau 2006;Lo and Lo 2014).…”
Section: Research Backgroundmentioning
confidence: 98%
“…Byun et al, (2011) argue that the compulsory adoption of EMI in Korea seems lacking a much-needed support system and appropriate lecturers, therefore the overall implementation of EMI across academic disciplines have formed the opinion that EMI can hinder student's comprehension of the teaching content. A meta-analysis conducted by Lo and Lo (2014) reveals that unlike EMI programs in other educational contexts (e.g., Canada or Europe), the EMI education in Hong Kong may experience a failure of academic achievement due to students' insufficient language training and teachers' pedagogical skills deficiency. On the other hand, a number of researches find there are insignificant differences in the academic performance when comparing L1 and EMI students.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%